Perception of Nurses Regarding Organizational Justice and Ethical Behavior; Organızational Culture in Hospitals - Zeynep Özsoy; Dilek Ekici (Baqiyatallah University of Medical Sciences, 2017)
Background: The organizational culture, justice, and ethical practices found in nursing services and health services have numerical superiority and a significant importance. Objective: This descriptive study aimed to determine the relationship among ethical behavior, organizational justice and culture in public and private hospitals. Methods: One hundred fifty-three nurses working for at least 6 months in a private or public hospital in Ankara participated in this study. The questionnaire used in this study consisted of three parts: participant demographic data, the ethical leadership scale, and organizational justice. Results: The perceptions regarding organizational culture and ethical behavior of nurses working in a private hospital were found to be greater than those of nurses working in a public hospital. A statistically significant relationship was found between the nurses' perceptions of organizational culture and justice. A similar relationship between perceptions of nurses regarding organizational culture and ethical behavior was also noted. The results showed that organizational culture explained 30% of the ethical leadership behavior of managers and 35% of organizational justice. Conclusion: The perceptions of nurses regarding justice and ethical behaviors are significantly affected by their work culture exposed in the case of increasing of non-ethic and non-fair behaviours it was the nurses perceive more strength and role culture.